Carisbamate blockade of T‐type voltage‐gated calcium channels. (23rd February 2017) - Kim, Do Young; Zhang, Fang‐Xiong; Nakanishi, Stan T.; Mettler, Timothy; Cho, Ik‐Hyun; Ahn, Younghee; Hiess, Florian; Chen, Lina; Sullivan, Patrick G.; Chen, S. R. Wayne; Zamponi, Gerald W.; Rho, Jong M.
Summary: Objectives: Carisbamate (CRS) is a novel monocarbamate compound that possesses antiseizure and neuroprotective properties. However, the mechanisms underlying these actions remain unclear. Here, we tested both direct and indirect effects of CRS on several cellular systems that regulate intracellular calcium concentration [Ca 2+ ]i . Methods: We used a combination of cellular electrophysiologic techniques, as well as cell viability, Store Overload‐Induced Calcium Release (SOICR), and mitochondrial functional assays to determine whether CRS might affect [Ca 2+ ]i levels through actions on the endoplasmic reticulum (ER), mitochondria, and/or T‐type voltage‐gated Ca 2+ channels. Results: In CA3 pyramidal neurons, kainic acid induced significant elevations in [Ca 2+ ]i and long‐lasting neuronal hyperexcitability, both of which were reversed in a dose‐dependent manner by CRS. Similarly, CRS suppressed spontaneous rhythmic epileptiform activity in hippocampal slices exposed to zero‐Mg 2+ or 4‐aminopyridine. Treatment with CRS also protected murine hippocampal HT‐22 cells against excitotoxic injury with glutamate, and this was accompanied by a reduction in [Ca 2+ ]i . Neither kainic acid nor CRS alone altered the mitochondrial membrane potential (ΔΨ) in intact, acutely isolated mitochondria. In addition, CRS did not affect mitochondrial respiratory chain activity, Ca 2+ ‐induced mitochondrial permeability transition, and Ca 2+ release from the ER. However, CRS significantly decreased Ca 2+ flux in human embryonic kidney tsA‐201 cells transfected with Cav 3.1 (voltage‐dependent T‐type Ca 2+ ) channels. Significance: Our data indicate that the neuroprotective and antiseizure activity of CRS likely results in part from decreased [Ca 2+ ]i accumulation through blockade of T‐type Ca 2+ channels.